Extremely rigorous subliminal paradigms demonstrate unconscious influences on simple decisions. Issue 1 (24th January 2014) - Snodgrass, Michael; Shevrin, Howard; Abelson, James A.
Abstract While showing unconscious influences on complex decisions is indeed difficult, relevant awareness in relatively simpler subliminal paradigms is more easily assessed. Utilizing objective detection (vs. more typical identification or classification) tasks to assess awareness overcomes longstanding residual methodological problems, and prior work using such methods (e.g., Snodgrass & Shevrin 2006) clearly shows unconscious influences on simple decisions.